2009
DOI: 10.1017/s0022377808007708
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of ion wakefields by electromagnetic pulses in dense plasmas

Abstract: Abstract. The excitation of electrostatic ion wakefields by electromagnetic pulses in a very dense plasma is considered. For this purpose, a wave equation for the ion wakefield in the presence of the ponderomotive force of the electromagnetic waves is obtained. Choosing a typical profile for the electromagnetic pulse, the form of the ion wakefields is deduced. The electromagnetic wave-generated ion wakefields can trap protons and accelerate them to high energies in dense plasmas.There are many proposals [1][2]… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that quantum effects can be important even in the classical regime [61,62]. The excitation of electrostatic wakefields in a quantum plasma by the ponderomotive force has been studied [63][64][65][66] and it has been found that the plasma number density plays an important role in the transition from wakefield generation to soliton formation [67].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that quantum effects can be important even in the classical regime [61,62]. The excitation of electrostatic wakefields in a quantum plasma by the ponderomotive force has been studied [63][64][65][66] and it has been found that the plasma number density plays an important role in the transition from wakefield generation to soliton formation [67].…”
Section: Introductionmentioning
confidence: 99%
“…For most practical applications, high-quality particle beams with high spatial quality and monoenergetic energy distribution are required. In order to produce high-quality beams from laser-based accelerators, numerous investigations have treated the subject experimentally and theoretically [1][2][3][4][5]. Among the wellknown laser-driven acceleration schemes, much work has been carried out studying the vacuum laser acceleration by an ultra-intense short laser pulse [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%